Utility Inspiratory Capacity by Simple Spirometry as an indirect Measure of Air Trapping - Alberto Herrejon; Julio Palop; Susana Herrera; Alejando Betancurt (Archives of Pulmonology and Respiratory Care - Peertechz Publications, 2017)
Objective: To  evaluate  the  utility  of  inspiratory  capacity  (IC)  measured  by  simple  spirometry  as  an indirect measure of air trapping. Method: Functional  residual  capacity  (FRC)  and  IC  were  determined,  respectively,  by  a  body plethysmography and by spirometry. Air trapping was defined by a FRC higher than 120%. Spearman's rho between IC and FRC is determined and the receiver operating characteristic (ROC curve) is calculated as predictive of air trapping for IC. The best cutoff of the overall test is calculated. Results: 148 patients were included with a mean FEV1 60% (SD 20%). There was significant correlation between IC and FRC with a Spearman rho -0.673 (p <0.0001). The area under the ROC curve for IC and FRC was 0.803 (95% CI 0.709 to 0.897). The optimal cutoff for predicting air trapping was given for a forced IC less than 80% of its theoretical value, with a sensitivity of 82%, a specificity of 73%, a positive predictivevalue of 73% and a negative predictive value 82%. Conclusions: Inspiratory  capacity  is  useful  in  the  assessment  of  air  trapping  and  may  determine  a cut below 80%.